Growth Parameters in Children with Transfusion-Dependent Thalassemia and Their Correlation with Serum Ferritin (Dhaka Shishu (Children) Hospital Journal, 2025)
Background: Thalassemia represents one of the most common hereditary genetic disorders in Bangladesh. Impaired growth is seen in children with transfusiondependent thalassemia which is thought to be the consequence of iron overload. Growth retardation affects the quality of life. Objective: To assess growth parameters in children with transfusion-dependent thalassemia and their correlation with serum ferritin. Methods: This cross-sectional study was carried out on 67 transfusion-dependent thalassemia patients aged between 5 to 18 years who attended the Department of Pediatric Hematology and Oncology and the Department of Transfusion Medicine in Bangabandhu Sheikh Mujib Medical University (BSMMU) from June 2020 to August 2021. Anthropometric measurements of children including age, sex, weight, and height were recorded, and Z scores and BMI were calculated. Serum Ferritin level was estimated for each of the participants. Statistical analysis of the results was obtained by using Statistical Packages for Social Sciences (SPSS version 22). Results: More than one-third of children with Transfusion-dependent thalassemia were underweight (44.7%) with stunted growth (40.3%). The mean serum ferritin levels were 2819.04±1085.48μg/l and 2913.44±1304.53μg/l in the beta-thalassemia and E-beta thalassemia groups respectively. The mean serum ferritin level was 2807.0±1271.9μg/l in normal weight, 2995.7±987.0 μg/l in underweight, and 3000.0±1504.7 μg/l in severely under-weight according to WAZ score. Similarly, the mean serum ferritin level was 2889.34±1209.2 μg/l in normal height, 2836.73±955.0 μg/l in stunted, and 2908.33±1415.2 μg/l in severely stunted according to HAZ score. The mean serum ferritin level was 2819.04±1085.48μg/l in BMI 0.05). Conclusion: There is no correlation between growth parameters with serum ferritin levels in children with transfusion-dependent thalassemia.DS (Child) H J 2023; 39(2): 88-92